ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA MANAJEMEN - Sri Dwi Ningsih; Mahdania Afria (STIE Kertanegara Malang, 2019)
This research was conducted to determine the company's management performance of PT. Telekomunikasi Indonesia Tbk. The 2014 to 2016 period is based on financial ratio analysis, which consists of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. And compare the company's management performance of PT. Telekomunikasi Indonesia Tbk. With similar companies to find out the company's performance in the average industry. This type of research is descriptive - quantitative research using secondary research data. Sourced from the official website of the Indonesia Stock Exchange in 2014 to 2016. The financial statements using library and analysis techniques used are financial ratio analysis consisting of liquidity ratios, solvency ratios, performance ratios, and profitability ratios to profit and loss statements and PT. Telekomunikasi Indonesia Tbk from 2014 to 2016. The results of the analysis conducted related to the company's provisions for the period 2014 to 2016 based on liquidity ratios through the calculation of the current ratio, fast ratio, and cash ratio show that the conditions are quite good but not stable because they have not reached number 2 so they cannot be sold as needed. Based on the solvency ratio, from the calculation of DER, DAR, and TIE shows a satisfactory figure, the company can meet the total demand with the total assets. Based on WKTO, TATO, ARTO, and FATO calculations in the performance ratio, it shows that the company's performance in a fairly stable and effective condition from each ratio does not need to be at a lower level and not too high. And based on calculations, profitability ratios that include calculations of NPM, GMP, ROA, ROE, and ROI show that the company is quite good in producing earnings that are quite low estimates. While the management performance of PT. Telekomunikasi Indonesia Tbk. When compared with companies that use financial ratio analysis, which shows a very good company compared to other companies, and the overall ratio value is above the average industry ratio